Cardiac remodeling from the fetus to adulthood. Issue 2 (13th February 2023) - Youssef, Lina; Castellani, Roberta; Valenzuela‐Alcaraz, Brenda; Sepulveda‐Martinez, Álvaro; Crovetto, Francesca; Crispi, Fàtima
Abstract: Prenatal cardiac remodeling refers to in utero changes in the fetal heart that occur as a response to an adverse intrauterine environment. In this article, we will review the main mechanisms leading to cardiac remodeling and dysfunction, summarizing and describing the major pathological conditions that have been reported to be related to this in utero plastic adaptive process. We will also recap the current evidence regarding the persistence of fetal cardiac remodeling and dysfunction, both in infancy and later in adult life. Moreover, we will discuss primary, secondary, and tertiary preventive measures and future clinical and research aspects. Abstract : The named "second hit hypothesis" postulates that a predisposed individual ‐that has already suffered a first hit during fetal life‐, postnatally, will more easily fail to cope with a second hit and will be at major risk of cardiovascular disease/failure.